CITY BRANDING KOTA BANDA ACEH: EVALUASI TOURIST PADA PEMILIHAN DESTINASI TOUR - Mohd. Fahrozi, Nurchalil (Departemen Manajemen, 2018)
The aim of this research is to evaluate the application of City Branding Programme which has been applied by Banda Aceh City from the tourist perspective who visited Banda Aceh City through the Attitude toward brand (X), brand image (Z), preference (Y). This research used quantitative approach, the number of respondents used are 110 respondents by using the purposive sampling technique. The collecting data was conducted by distributed the questioners to respondents who fulfil the requirement of this research. Measurement model in this research used Partial Least Square (PLS). The Finding of this research showed that the Attitude toward brand (X) have positive influence to preference (Y), the Attitude toward brand (X) have positive influence to the brand image (Z), the brand image variable (Z) have positive influence to preference (Y), and the brand image (Z) partially influence the Attitude toward brand (X) and preference (Y). Therefore, even the variable show the positive influence toward the application of City Branding in Banda Aceh City especially in tourism sector, the government still have to improve and increase the service and tour facilitations in Banda Aceh to give the good experience to the tourist and can build the preference of the tourist to visit Banda Aceh City in the future.Keyword: City Branding, Attitude toward brand, brand image, preference, Banda Aceh